2013
DOI: 10.1002/esp.3385
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopes in the rivers from the Lesser Antilles: origin of the carbonic acid consumed by weathering reactions in the Lesser Antilles

Abstract: International audienceIn this paper, we use carbon isotopes in the dissolved load of rivers from the Lesser Antilles volcanic arc (Guadeloupe, Martinique and Dominica islands) to constrain the source of the carbon dioxide (CO2) involved in the neutralization reactions during water-rock interactions. The d13C data span a large range of variations, from -19% to -5 _ 2% for DIC (dissolved inorganic carbon) concentrations ranging from 11 mM to 2000 mM. Coupled with major element concentrations, carbon isotopic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 63 publications
2
44
0
Order By: Relevance
“…Recent studies of tectonically active settings suggest that weathering in the deep CZ may be particularly important in determining the strength of connections between climate and tectonics (Tipper et al , ; Calmels et al , ; West, ). In this special issue, Rivé et al () documented connections between weathering and volcanically sourced carbon dioxide using carbon isotopes in stream water from the Lesser Antilles. They found that deeply sourced carbon dioxide plays a key role in the rapid rates of silicate weathering that they observed on these islands.…”
Section: Observations Of the Deep Czmentioning
confidence: 99%
“…Recent studies of tectonically active settings suggest that weathering in the deep CZ may be particularly important in determining the strength of connections between climate and tectonics (Tipper et al , ; Calmels et al , ; West, ). In this special issue, Rivé et al () documented connections between weathering and volcanically sourced carbon dioxide using carbon isotopes in stream water from the Lesser Antilles. They found that deeply sourced carbon dioxide plays a key role in the rapid rates of silicate weathering that they observed on these islands.…”
Section: Observations Of the Deep Czmentioning
confidence: 99%
“…In addition to biogenic contributions from the surface, dissolved CO 2 and CH 4 in regional groundwater can originate from volcanic degassing, nonvolcanic escape of gases from the upper mantle, intrusive magma chambers, carbonate‐bearing rocks in the crust, hydrocarbon accumulations [ Mörner and Etiope , ], and remineralization of ancient sedimentary organic matter [ Lovley and Anderson , ; Park et al ., ; Liu et al ., ]. Aquifers transporting high concentrations of dissolved C have been identified in numerous places around the world, for example, Portugal [ Cruz and Amaral , ], the Canary Islands [ Marrero et al ., ], the United States [ Evans et al ., ; Kampman et al ., ], Japan [ Yamada et al ., ], Canada, Costa Rica, Italy [ Genereux et al ., , and references therein], the Lesser Antilles [ Rivé et al ., ], and the Slovak Republic [ Kucharič et al ., ]. However, little is known about the fate of that C once it discharges into surface waters and its effects on C balances of the aquatic and surrounding terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Results may have relevance for the carbon cycle and climate studies exploring the emplacement of large igneous provinces like the CAMP (Schaller et al, 2012) or the Deccan Traps (Caldeira and Rampino, 1990) with production of large basaltic areas within a short time. However, the biological contribution to CO 2 drawdown, via elevated fertilization effects, e.g., P or Si release due to weathering and elevated CO 2 in the atmosphere, should be taken into account, too.…”
Section: Models For Comparisonmentioning
confidence: 92%
“…The sensitivity of basalt weathering to climate change (Dessert et al, 2001Coogan and Dosso, 2015;Li et al, 2016) supports a negative weathering feedback in the carbon cycle that maintains the habitability of the Earth's surface over geological timescales (Walker et al, 1981;Berner et al, 1983;Li and Elderfield, 2013). Changes in volcanic weathering fluxes due to emplacement of large volcanic provinces or shifts in the geographic distribution of volcanic fields associated with continental drift may have contributed to climate change in the past (Goddéris et al, 2003;Schaller et al, 2012;Kent and Muttoni, 2013).…”
Section: Introductionmentioning
confidence: 87%